The Intra-Cochlear Impedance-Matrix (IIM) test for the Nucleus® cochlear implant - Hey, Matthias; Boehnke, Britta; Dillier, Norbert; Hoppe, Ulrich; Eskilsson, Gunnar; Lowgren, Karolina; Cullington, Helen; Mauch, Herbert; Mueller-Deile, Joachim (Biomedizinische Technik, 2015)
To describe the principles and operation of a new telemetry-based function test for the Nucleus® cochlear implant, known as the CS19 Intra-Cochlear Impedance Matrix (IIM) and to present results from a multicentre clinical study to establish reproducibility (test-retest reliability) and normative ranges.The IIM test measures bipolar impedances between all electrode pairs and employs a normalization procedure based on common ground impedances in order to identify abnormal current paths among electrodes. Six European clinics collected IIM data from a total of 192 devices.Reproducibility was high between initial and repeat measurements. The normative analysis demonstrated narrow ranges among devices after normalization of impedance data. The IIM is able to identify abnormal current paths that are not evident from standard impedance telemetry and may otherwise only be found utilising average electrode voltage measurements (AEV).The IIM test was found to be straightforward to perform clinically and demonstrated reproducible data with narrow ranges in normally-functioning devices. Because this test uses a very low stimulation level the IIM test is well suited for children or multiply handicapped CI users who cannot reliably report on their auditory percepts. The new algorithms show potential to improve implant integrity testing capabilities if implemented in future clinical software.
EVALuna2:20025